Potential Cultural Strategy for Preventing National Resilience from Terrorism in Indonesia - Agustanto, Pulung; Runturambi, Arthur Josias; Puspitasari, Puspitasari (International Journal Labs, 2025)
Indonesia has increasing threats to its national resilience stemming from the ascendance of radical ideologies and the widespread impact of globalized popular culture, both of which erode traditional values and social cohesion. This study investigates the utilization of cultural strategy as a preventive framework to enhance national identity and mitigate ideological risks. The study utilized a qualitative research design based on a constructivist paradigm, incorporating literature reading and document analysis, with an emphasis on state policies and cultural expressions, specifically dangdut koplo music. The results indicate that cultural components, when included in national policy, serve as instruments of soft power that bolster cohesion and ideological temperance. The findings underscore the necessity of incorporating cultural expressions into policy and educational frameworks to ensure enduring resilience. The discourse underscores that cultural strategy is integral to national defense, providing a repeatable framework for other multicultural civilizations facing analogous sociocultural upheavals.